Evaluation and management of postpartum hemorrhage: consensus from an international expert panel - Abdul-Kadir, Rezan; Hofer, Stefan (Transfusion, 2014)
Background: Postpartum hemorrhage (PPH) remains one of the leading causes of maternal morbidity and mortality worldwide, although the lack of a precise definition precludes accurate data of the absolute prevalence of PPH. Study Design and Methods: An international expert panel in obstetrics, gynecology, hematology, transfusion, and anesthesiology undertook a comprehensive review of the literature. At a meeting in November 2011, the panel agreed on a definition of severe PPH that would identify those women who were at a high risk of adverse clinical outcomes. Results: The panel agreed on the following definition for severe persistent (ongoing) PPH: “Active bleeding >1000 mL within the 24 hours following birth that continues despite the use of initial measures including first-line uterotonic agents and uterine massage.” A treatment algorithm for severe persistent PPH was subsequently developed. Initial evaluations include measurement of blood loss and clinical assessments of PPH severity. Coagulation screens should be performed as soon as persistent (ongoing) PPH is diagnosed, to guide subsequent therapy. If initial measures fail to stop bleeding and uterine atony persists, second- and third-line (if required) interventions should be instated. These include mechanical or surgical maneuvers, i.e., intrauterine balloon tamponade or hemostatic brace sutures with hysterectomy as the final surgical option for uncontrollable PPH. Pharmacologic options include hemostatic agents (tranexamic acid), with timely transfusion of blood and plasma products playing an important role in persistent and severe PPH. Conclusion: Early, aggressive, and coordinated intervention by health care professionals is critical in minimizing blood loss to ensure optimal clinical outcomes in management of women with severe, persistent PPH.
Gesehen am 11.08.2020